2011
DOI: 10.1096/fj.10-169854
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 receptor drives osteoclast fusion by increasing the extracellular adenosine concentration

Abstract: Defects in bone homeostasis are a major health problem. Osteoclast differentiation and activation have a crucial role in bone remodeling in health and disease. Osteoclasts are bone-resorbing cells derived from mononuclear phagocyte progenitors. The key event in osteoclast formation is fusion of mononucleate precursors to form mature multinucleated osteclasts. Here we provide evidence of an absolute requirement for the P2X7 receptor, ATP release, and adenosine signaling in human osteoclast formation, as shown b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(103 citation statements)
references
References 48 publications
8
92
2
1
Order By: Relevance
“…The pathways involved in the purinergic control of bone metabolism are thus probably complex and the roles played by the three facets involved (metabolising enzymes, P2 receptors, P1 receptors) are probably intertwined. Evidence of this has already been published by Pellegatti and co-workers [19] who show that the P2X7 receptor drives osteoclast fusion by increasing extracellular adenosine concentration. Such complex processes could, of course, be modulated in disease states such as osteoporosis and arthritis.…”
Section: Commentarymentioning
confidence: 69%
“…The pathways involved in the purinergic control of bone metabolism are thus probably complex and the roles played by the three facets involved (metabolising enzymes, P2 receptors, P1 receptors) are probably intertwined. Evidence of this has already been published by Pellegatti and co-workers [19] who show that the P2X7 receptor drives osteoclast fusion by increasing extracellular adenosine concentration. Such complex processes could, of course, be modulated in disease states such as osteoporosis and arthritis.…”
Section: Commentarymentioning
confidence: 69%
“…Consistent with these findings, A 1 receptor knockout mice display increased bone mineral density and resistance to ovariectomyinduced bone loss [284]. ATP released through P2X7 receptors acts as the major source of adenosine that enhances mature osteoclast function via A 2A receptors [273]. However, a later study showed that adenosine, acting through A 2A receptors, inhibited osteoclast differentiation [285].…”
Section: P1 Receptors Adenosine and Osteoclastsmentioning
confidence: 80%
“…The P2X7 receptor may additionally play a role in the intercellular communication between osteoblasts and osteoclasts [271], cytoskeletal reorganisation at the sealing zone and the delivery and secretion of lytic granules into the resorption lacunae [272]. Recently, it was shown that ATP release from osteoclasts is mediated via the P2X7 receptor [211,273]. Thus, this receptor is thought to drive osteoclast fusion by increasing the concentration of extracellular adenosine (via breakdown of released ATP) [273] (see Fig.…”
Section: Functional Effects Of P2 Receptor-mediated Signalling In Ostmentioning
confidence: 99%
See 1 more Smart Citation
“…Both osteoblasts and osteoclasts have been reported to express all four P1 receptor subtypes [23][24][25][26][27]. However, the actions of extracellular adenosine on bone cells appear to be somewhat less clear-cut than those of ATP.…”
Section: Introductionmentioning
confidence: 99%